I want to evaluate the following double sum (from blackpenredpen's video) $$\sum_{m=1}^{\infty}{\sum_{n=1}^{m}\frac{1}{2^{m+n}}}$$ In the video, he is showing how to change the order of the sums, but I want to do this normally.

I am pretty confident the inner sum is $\frac{2^m-1}{2^{2m}}$ by geometric series although I am not that good at this subject. Then, how would I evaluate the outer sum?


Yes indeed we have that


and then

$$\sum_{m=1}^{\infty} \frac{2^m-1}{2^{2m}}=\sum_{m=1}^{\infty} \frac{1}{2^{m}}-\sum_{m=1}^{\infty} \frac{1}{2^{2m}}=\sum_{m=1}^{\infty} \frac{1}{2^{m}}-\sum_{m=1}^{\infty} \frac{1}{4^{m}}$$

and we can use geometric series again.

  • $\begingroup$ oh right, thank you. All the summation "rules" are still new for me. $\endgroup$ – aradarbel10 Nov 30 '19 at 21:56
  • $\begingroup$ @aradarbel10 You did a proper evaluation for the first sum, yu shouldn't have difficulties to obtain the result. You are welcome! Bye $\endgroup$ – user Nov 30 '19 at 21:58

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.